Scurvy, all the faces you can see: our experience and review of the literature - Fabio Toscano; Giuseppina Zirilli; Simone Foti Randazzese; Mariagrazia Carlino; Romina Gallizzi; Malgorzata Wasniewska; Mariella Valenzise (Italian Journal of Pediatrics)
Abstract Background In the recent past an incremental incidence of scurvy has been reported in the pediatric population, especially in children with neuropsychiatric disorders and a selective diet. Musculoskeletal manifestations, such as limp and refusal to walk, usually represent the main causes of access in the emergency room. Nowadays, new patterns of manifestations have been demonstrated, such as hematological and cardiological changes including pulmonary hypertension, rarely resulting in potential lethal complications. Case presentation : We describe five pediatric patients affected by developmental delay or autism, with a restrictive diet, diagnosed with scurvy during the hospitalization: 3 pre-school aged boys presenting with typical clinical presentation, due to severe malnutrition; a 6-year-old girl with refusal to walk and a very high titre of inflammatory markers, without typical signs of scurvy; a 4-year-old boy with severe pulmonary hypertension, rarely related to vitamin C deficiency. In all the cases, a prompt resolution of the symptoms after the administration of vitamin C has been observed, confirming the diagnosis. Conclusion At present, scurvy is a more contemporary condition than previously thought. It is fundamental to recognize both typical and atypical manifestations to avoid delay of diagnosis or rarely life-threatening complications.